Accuracy assessment of mobile laser scanning elevation data in different vegetation areas - Kokamägi, Kaupo; Liba, Natalja; Must, Kristo; Sirk, Martin (International Conference “Environmental Engineering”, 2017)
Due to the overall development of technology, laser scanning has reached a new level. During the last decade, all the different technologies necessary for mobile laser scanning, have been developed. Due to the fact that mobile laser scanning brings the need to process very large amounts of data, development of computers and software is also very important. The aim of current research was to assess the accuracy of mobile laser scanning elevation data in different vegetation areas and to explore if mobile laser scanning could be used as an alternative to aerial laser scanning. This article only covers the data collecting, processing and accuracy assessment aspects of the research. Data used in current study was collected in summer of 2015, during mobile laser scanning of Põltsamaa-Kärevere section of E263 route (Tallinn-Tartu-Võru-Luhamaa). Three smaller, differently vegetated, sections were picked from the large project to study the accuracy of elevation data. For accuracy assessment, the mobile laser scanning elevation data was compared to the checkpoints measured with GNSS (Global Navigation Satellite Systems) device. Ground profiles were drawn based on mobile laser scanning data. For objective assessment, accuracy of mobile laser scanning elevation data was compared to accuracy of ground profile elevation data and aerial laser scanning elevation data. The study found that the RMSE (Root Mean Square Error) in the I section, which was a field vegetated with 1 metre high crop, was 0,98 metres. RMSE in the II section, which was a pasture with low and sparse vegetation, was 0,23 metres. RMSE in the III section, which contained a bushy ditch and a field behind it, was 0,61 metres. Results show that the accuracy of mobile laser scanning elevation data depends substantially on the density of vegetation in scanned areas and that drawing ground profiles reduced the RMSE of mobile laser scanning elevation data. Results show that the accuracy of mobile laser scanning elevation data depends substantially on the density of vegetation in scanned areas. On this basis it can be concluded, that the most reasonable time to conduct mobile laser scanning would be during a season, when vegetation is the sparsest. It can also be concluded that drawing ground profiles makes mobile laser scanning data more accurate.
Keywords: laser scanning; mobile laser scanning; accuracy of elevation data